Revolusi Digital dan Merdeka Belajar: Meningkatkan Daya Saing Siswa di Era Teknologi - Fahrina Yustiasari Liriwati (Journal Innovation In Education, 2023)
The digital revolution has fundamentally changed the educational paradigm, influencing the way of learning, teaching and interacting in the educational environment. In responding to the challenges and opportunities presented by this technological era, the concept of "Freedom to Learn" emerged as an approach that empowers students to be active and independent in the learning process. This article discusses how the Merdeka Belajar approach can increase students' competitiveness in the technological era by combining the potential of the digital revolution in education. In the initial stage, the article introduces the concept of Merdeka Belajar which places students at the center of the learning process. By giving students the freedom to choose the time, method and learning materials according to their interests and abilities, this approach aims to increase students' motivation, creativity and participation in learning. Next, the article discusses the use of technology in education, including e-learning, learning videos, online learning platforms and educational applications. The use of this technology allows students to access various learning resources more easily, expand the range of knowledge, and increase learning efficiency. Technology integration is key in supporting the implementation of the Merdeka curriculum and providing an interactive and interesting learning experience for students. In addition, the article highlights the importance of developing digital literacy abilities, technological skills, and an understanding of digital ethics for students in an era of ever-developing technology. Merdeka Belajar plays an important role in helping students hone these skills, so they can be better prepared to face the challenges of the digital world. The article also examines the challenges and obstacles in combining Merdeka Belajar with technology, such as limited access to technology, lack of training for teachers, and concerns about data security . Solutions and strategies to overcome this obstacle are also discussed in the article. In its conclusion, the article underlines the importance of adopting the Independent Learning concept integrated with technology to bring innovation in education. This approach can improve the quality and relevance of learning, prepare students to face the challenges of the technological era, and increase their competitiveness in facing an increasingly digital future.